A Fuzzy Analytic Hierarchy Process Based Particle Swarm Optimization for Multi-Objective Domain Optimal Control Problems - Qiyu Liu, Longjin Lv (Forest Chemicals Review, 1970)
Aiming to solve the multi-objective domain optimal control problem for a heat conduct system, this study proposes a numerical computation method based on a hybrid particle swarm optimization (PSO) algorithm integrated with fuzzy analytic hierarchy process (FAHP). After being discretized by finite element method (FEM) and control parameterization, this problem is solved by a hybrid PSO in which global optimal particle is selected by AHP based on fuzzy consistent judgment matrices. The numerical simulations are presented, and the result shows the proposed method can provide a feasible and effective solution for the multi-objective domain optimal control problem for the heat conduct system.